2017
DOI: 10.1111/iwj.12782
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the daily activity of patients with diabetic foot ulcers compared to controls in their free‐living environments

Abstract: The aims of our study were to investigate multiple daily activity outcomes in patients with diabetic foot ulcers (DFU) compared to diabetic peripheral neuropathy (DPN) and diabetes (DM) controls in their free-living environments. We examined daily activity outcomes of 30 patients with DFU, 23 DPN and 20 DM. All patients wore a validated multi-sensor device for > 5 days (>22 hours per day) to measure their daily activity outcomes: steps, energy expenditure (kJ), average metabolic equivalent tasks (METs), physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 47 publications
3
41
0
Order By: Relevance
“…A validation set of 30 publications was created, including key studies known to the authors published since our previous search (July 29, 2014) . Using this set, the search strings used were validated; ie, each publication had to be identified before the search strings were used in this systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…A validation set of 30 publications was created, including key studies known to the authors published since our previous search (July 29, 2014) . Using this set, the search strings used were validated; ie, each publication had to be identified before the search strings were used in this systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…With advances in signal processing and multi‐sensor devices, it is now possible to comprehensively monitor activity beyond counting steps. This includes measurements of total weight‐bearing activity, bouts of weight‐bearing activity, and activity intensity . Najafi et al found that neuropathic patients spent approximately three folds as much time weight‐bearing per day as walking, and that daily standing time may be predictive of worse DFU healing outcomes .…”
Section: Technologies For Effective and Personalized Prescription Of mentioning
confidence: 99%
“…This includes measurements of total weight-bearing activity, bouts of weight-bearing activity, and activity intensity. [28][29][30] Najafi et al 31 found that neuropathic patients spent approximately three folds as much time weight-bearing per day as walking, and that daily standing time may be predictive of worse DFU healing outcomes. 32 In a recent exploratory study, 33 Figure 3).…”
Section: Technologies For Effective and Personalized Prescription Omentioning
confidence: 99%
“…23 These calculations suggested 25 participants were required in each group to determine a statistical difference for daily steps which is considered a surrogate marker of daily activity. 23,24…”
Section: Sample Sizementioning
confidence: 99%
“…23 No further advice was provided as the study aim was to observe typical daily activity of participants in their normal free-living everyday environment. 23 At least five days of data from wearing the device for at least 22 hours on each of those days, with at least one of those days being a weekend day, was required to be eligible for the participant's data to be included, as this period has been previously validated to be representative of typical daily activity. [31][32][33][34] Days in which a participant wore the device for less than 22 hours were excluded.…”
Section: Participant Characteristicsmentioning
confidence: 99%